2015
DOI: 10.1038/srep14557
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Mechanism for Regulation of Bcl-2 protein Noxa by phosphorylation

Abstract: We showed previously that phosphorylation of Noxa, a 54-residue Bcl-2 protein, at serine 13 (Ser13) inhibited its ability to promote apoptosis through interactions with canonical binding partner, Mcl-1. Using EPR spectroscopy, molecular dynamics (MD) simulations and binding assays, we offer evidence that a structural alteration caused by phosphorylation partially masks Noxa’s BH3 domain, inhibiting the Noxa-Mcl-1 interaction. EPR of unphosphorylated Noxa, with spin-labeled amino acid TOAC incorporated within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…Due to oxidative stress, the mitochondrial dysfunction by accumulation of intracellular reactive oxygen species (ROS) has been associated with apoptosis. As a well-known anti-apoptotic gene, Bcl-2 stabilizes mitochondria, blocks the classic apoptotic pathways, and suppresses autophagy through binding with Beclin 1 13 14 15 16 17 . In the current study, we found that Bcl-2 was controlled by IGF-1 in UUO, as a major mechanism for the renal epithelial cells to resist the injury and survive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to oxidative stress, the mitochondrial dysfunction by accumulation of intracellular reactive oxygen species (ROS) has been associated with apoptosis. As a well-known anti-apoptotic gene, Bcl-2 stabilizes mitochondria, blocks the classic apoptotic pathways, and suppresses autophagy through binding with Beclin 1 13 14 15 16 17 . In the current study, we found that Bcl-2 was controlled by IGF-1 in UUO, as a major mechanism for the renal epithelial cells to resist the injury and survive.…”
Section: Discussionmentioning
confidence: 99%
“…Bid, Bak, Bad, and apoptosis suppressors, e.g. B-cell lymphoma 2 (Bcl-2)1314151617. Bcl-2 is the founding member of the Bcl-2 family of regulator proteins that regulate cell death (apoptosis), by either inducing (pro-apoptotic) or inhibiting (anti-apoptotic) apoptosis1314151617.…”
mentioning
confidence: 99%
“…In this study, we have used solid-phase peptide synthesis (SPPS), circular dichroism (CD), and EPR to detect the structural dynamics of RyRp, bound to apoCaM and bound to Ca 2þ -CaM in solution. EPR is a powerful technique for investigating structural changes in proteins and protein/enzyme complexes in response to regulatory modifications (19)(20)(21). In these studies, peptides are typically prepared by 9-fluorenylmethoxycarbonyl SPPS (22), which permits the incorporation of nonnatural amino acids into the peptide sequence, including the spin-labeled amino acid 2,2,6,6-tetramethylpiperidine-1-oxyl-4-amino-4-carboxylic acid (TOAC).…”
Section: Introductionmentioning
confidence: 99%
“…39 As a final recent example, simulations have detected a claw-like structure in the long-time dynamics of a small, apoptosis-related intrinsically disordered protein (IDP) known as Noxa. 40 Include Figure 2 here.…”
Section: Introductionmentioning
confidence: 99%